2021
DOI: 10.1007/s00261-021-02964-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel deep learning-based noise reduction technique for prostate magnetic resonance imaging

Abstract: Introduction Magnetic resonance imaging (MRI) has played an increasingly major role in the evaluation of patients with prostate cancer, although prostate MRI presents several technical challenges. Newer techniques, such as deep learning (DL), have been applied to medical imaging, leading to improvements in image quality. Our goal is to evaluate the performance of a new deep learning-based reconstruction method, “DLR” in improving image quality and mitigating artifacts, which is now commercially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 16 publications
5
38
2
Order By: Relevance
“…There have been two PCa studies with the use of DLR to our knowledge: one demonstrated the feasibility of prostate MRI with reduced acquisition time by 65% (4 minutes 37 seconds for axial T2WI using conventional protocol vs. 1 minute 38 seconds for axial T2WI with short scan time and DLR) in 30 men 22 and the other showed the image quality improvement on standard MRI for 31 men. 23 In our study, although fast MRI with DLR demonstrated better subjective image scores than fast MRI, it showed significantly lower image quality scores than conventional MRI-contrary to the study by Gassenmaier et al showing better image quality scores with the use of fast MRI with DLR. 22 Since image quality can be affected by various acquisition parameters, including parallel imaging acceleration factor, echo train length, TR, echo time, or number of excitations, 29 the use of different parameters may have attributed to those conflicting results with the study by Gassenmaier et al Optimal modification of these technical parameters for the DLR approach may enable image quality improvement of fast MRI, relative to conventional MRI.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…There have been two PCa studies with the use of DLR to our knowledge: one demonstrated the feasibility of prostate MRI with reduced acquisition time by 65% (4 minutes 37 seconds for axial T2WI using conventional protocol vs. 1 minute 38 seconds for axial T2WI with short scan time and DLR) in 30 men 22 and the other showed the image quality improvement on standard MRI for 31 men. 23 In our study, although fast MRI with DLR demonstrated better subjective image scores than fast MRI, it showed significantly lower image quality scores than conventional MRI-contrary to the study by Gassenmaier et al showing better image quality scores with the use of fast MRI with DLR. 22 Since image quality can be affected by various acquisition parameters, including parallel imaging acceleration factor, echo train length, TR, echo time, or number of excitations, 29 the use of different parameters may have attributed to those conflicting results with the study by Gassenmaier et al Optimal modification of these technical parameters for the DLR approach may enable image quality improvement of fast MRI, relative to conventional MRI.…”
Section: Discussioncontrasting
confidence: 88%
“…20,21 For PCa, there have been two feasibility studies using DLR on MRI with short acquisition time (i.e., fast MRI); these have demonstrated improvement in overall image quality, reduction of artifacts, and good lesion detectability. 22,23 However, those were predominantly based on subjective image quality analysis in a small number of patients. Furthermore, they did not evaluate the diagnostic performance with regard to evaluation of tumor size or extraprostatic extension (EPE), which may be closely related to image quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in recent studies on prostate MRI that DL can be applied for cancer detection and classification and also for registration with histopathological images [10,11,23,24]. Wang et al demonstrated that DL could also be applied for the omission of endorectal coils in mpMRI without compromising the image quality regarding noise [25]. However, one of the most important recent developments regarding DL is related to MRI acquisition times.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DL techniques systematically reducing acquisition times might be the key for overcoming shortness of MR scanner capacities and improve healthcare and patient care. DL image reconstruction can not only be used for reduction of acquisition time, but also for improvement of image quality and improvement of patient comfort as it was presented by Wang et al in prostate MRI [ 39 ].…”
Section: Deep Learning Applications In Radiologymentioning
confidence: 99%